Infrastructure upgrades and foreclosure with coexistence of service-based and facility-based firms - Noriaki Matsushima; Keizo Mizuno (Osaka University, Institute of Social and Economic Research (ISER), 2012)
We investigate the incentives for facility-based firms to invest in infrastructure upgrades and to foreclose service-based firms. We focus on asymmetric regulation regarding servicebased firms' access to the infrastructure held by a facility-based firm. Spillovers from the infrastructure upgrades made by a regulated facility-based firm on service-based firms play a key role in the incentives for making these upgrades. The spillover effect can enhance the incentives for the regulated facility-based firm to make upgrades if access prices are not regulated. The existence of rival facility-based firms strengthens the incentives for a regulated facility-based firm to make infrastructure upgrades, especially when the spillover effect is significant. Furthermore, if access prices are not regulated, the existence of rival facility-based firms weakens the incentives for a regulated facility-based firm to foreclose service-based firms.
Keywords: L43; L51; L96; 330; investment; access; service-based firm; facility-based firm; Investition; Telekommunikationsnetz; Markteintritt; Monopol; Regulierungstheorie